Mechanical gear footstep power generation using a mini generator with buck and boost selectors - Sutikno, Tole; Fernando, Rizki; Pamungkas, Anggit; Purnama, Hendril Satrian; Baswara, Ahmad Raditya Cahya (Institute of Advanced Engineering and Science, 2023)
In this research, we intend to build a floor-based power plant that produces energy using a mechanical generator drive. The drive system uses a two-gear transmission system with a different number of teeth, resulting in varying torque and speed. The large gear will stick directly to the floor, causing it to spin when the floor is stepped on, and then the small gear will spin the generator quickly. The buck and boost selector systems are powered by fluctuating voltage from the generator. If the voltage produced by the generator is greater than 5 V, the system will reduce it; otherwise, the system will increase the voltage. This selector system uses several modifications of the current circuit between rectifiers, which function to rectify the generator output when the generator rotation changes, a voltage divider is useful for dividing the generator output voltage. The pressure before and after the selector system was measured by applying force on the floor to 15 people with varying loads. The result shows that the buck and boost selector system can work properly, and the nominal output voltage of the generator is around 5 V as needed.